An Improved Data Mining Model for Predicting the Impact of Economic Fluctuations. (31st March 2022) - Zhou, Liting; Chen, Qiang; Zhu, Tianyu
Abstract : In order to explore the influencing factors of economic fluctuations, this article combines data mining technology to mine the factors that affect economic fluctuations and introduces financial network theory to the transfer problem of investment strategies, which provides an effective research method for economic behavior research. Moreover, this article calculates the fund network parameters from a quantitative perspective by constructing the topological characteristic index of the financial network to illustrate the influence of the degree of network evolution and the time scale. In addition, this article constructs an economic fluctuation data mining model based on economic fluctuations and uses data to verify the effects of the method proposed in this article. The experimental results show that the data mining method proposed in this article can play an important role in the analysis of factors affecting economic fluctuations and accurately mine the relevant factors that affect the economy.